2012
DOI: 10.1017/s0021932012000600
|View full text |Cite
|
Sign up to set email alerts
|

Body Height and Socioeconomic Status of Females at Different Life Stages

Abstract: Adult height reflects long-term nutritional status and exposure to infectious diseases, both of which are influenced by socioeconomic factors. Very little research has been done on these inequalities from a longitudinal perspective. This paper explores the links between body height at different life stages and socioeconomic characteristics. Data were obtained from 1008 Polish schoolgirls aged 16-18 years for whom earlier data on height were available. The height of each subject was measured. Socioeconomic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…The Wronka study (32) concluded that socioeconomic status was related to body height, and that variation in height was the result of the living conditions during the first years of life. In contrast, Singh et al (23) found a weak association between income and stature, but the association could be modified by the effect of education.…”
Section: Discussionmentioning
confidence: 99%
“…The Wronka study (32) concluded that socioeconomic status was related to body height, and that variation in height was the result of the living conditions during the first years of life. In contrast, Singh et al (23) found a weak association between income and stature, but the association could be modified by the effect of education.…”
Section: Discussionmentioning
confidence: 99%
“…Although it varies among countries, the beginning of puberty and thus of the final growth spurt can be recognized as being initiated by menarche in girls and secondary sexual characteristics in boys and lasting for nearly 2 years (Cole, 2000(Cole, , 2003Wells, 2012;Ezzati & NCD-RisC, 2016). Chile has experienced a reduction in the age of puberty appearance, mainly due to improvements in living conditions, as it has been reported that well-nourished children from families with good socioeconomic conditions experience the growth spurt earlier than malnourished children from families with poor living conditions (Wronka, 2015). Most Chilean girls experience menarche at 13 years old and boys experience the appearance of secondary sexual characteristics at 15 years old (Valenzuela & Avendaño, 1979;Ivanovic & Ivanovic, 1988;Burrows et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The only information available in NFHS data that could indicate childhood nutritional stress is height (in centimetres, measured by trained survey personnel), which is used here as an index of childhood health status. Adult height is known to be to a large extent determined by gestational and early childhood conditions (Case & Paxson, 2010;Wronka, 2013), particularly in developing countries where the influence of genetic factors for completed height is less important than in more affluent environments (Silventoinen, 2003). A number of studies have come to the conclusion that nutrition and infections primarily influence adult size by influencing growth attainment during fetal life and early infancy when nutritional resources are derived primarily from the mother's body, thus linking adult size in the present generation with matrilineal nutritional history (Kuzawa, 2005(Kuzawa, , 2007Wells, 2007;Kuzawa & Quinn, 2009).…”
Section: Independent Variablesmentioning
confidence: 99%